The effect of a morning priming session of afternoon performance - FERGUS NUTT (2022)
Introduction: Match play within professional cricket commences at a variety of times during the day, with the shorter ‘white ball’ formats often starting anywhere from 11:00 to 19:30. This presents large windows of opportunity for pre-competition strategies to be utilised to improve performance. Salivary hormones, in particular testosterone, exhibit a circadian rhythm over the waking day, falling up to 50% to a nadir at 20:00. With salivary testosterone concentrations showing strong links with neuromuscular, cognitive and motivational benefits, the ability to optimise those natural levels could be a way to improve an athlete’s match day performance. Engaging in a bout of exercise prior to competition has been used by sports teams to prime the body, with the purpose to enhance performance. Methods: In this study, a group of 21 professional male cricket players (aged: 26  6 years, body mass: 88.1  4.4 kg, height: 184  3.6 cm) engaged in an investigation with the aim to compare the effects of 2 morning priming protocols on markers of afternoon performance. Following a randomised-counterbalance design, the players were split into groups of 4. The control day consisted of the players reporting for the afternoon tests (Readiness To Perform questionnaire [RTP], Stroop Test, countermovement jump [CMJ] and Run-two sprint at  15:00, with 30min slots for each group. The experimental trials consisted of groups arriving at  9:00 with 30min slots, to engage in either the Trap bar deadlift protocol (4 reps at 50%, 70%, 80%, 3 x 4 at 85% 1RM) or repeated Sprint session (6 x 35.4m with a 180 turn at the midpoint) with a 30s recovery, roles were reversed following a 7-day break; participants then rested for 5h and returned to completed the afternoon performance tests. Results: Run-two sprint time was significantly reduced (p < 0.001) (CON = 5.99  0.17s, Sprint = 5.94  0.17s, Trap bar = 5.91  0.17s), Trap bar saw further reductions when compared to the Sprint (p = 0.032). Only the Trap bar protocol saw a significant increase in CMJ Jump height (JH) (p = 0.021) (CON = 43.8  6.8cm, Sprint = 45.0  7.3cm, Trap bar = 45.2  6.5cm). There was no significant correlation between absolute (p > 0.05) or relative strength (p > 0.05) and the effectiveness of the priming strategies on neuromuscular performance. Both Sprint and Trap bar expressed significant reductions in time to complete the Stroop test (p < 0.05) (CON – 51.1  4.7s, Sprint – 48.4  3.6s, Trap bar – 47.9  2.8s), with Trap bar again reporting further reductions compared to Sprint (p < 0.05). Whilst the trials demonstrated a significant impact on the athletes’ afternoon neuromuscular and cognitive performance, their readiness to perform scores were unaffected (p > 0.05). Conclusion: Performing morning exercise is associated with afternoon neuromuscular and cognitive performance benefits, with no detriment to the readiness to perform.